Experiences of distortions to the passage of time during the Argentinian Covid-19 pandemic - Brenlla, María Elena (2022)
The Coronavirus-19 global pandemic has forced many governments around the world to enforce “lockdowns” to curtail the spread of the virus. Studies conducted in the UK, France, Italy and Brazil have demonstrated that one consequence of these lockdowns is significant distortion to the speed of the passage of time. The current study sought to establish how the passage of time was experienced during the Argentinian lockdown. An online questionnaire wasusedtomeasurepassageoftimejudgments forthe day and theweek, physical activity, satisfaction with social interaction, the extent to which daily routines had changed due to covid and demographic data. The results show that distortions to the passage of time were widely experienced during the lockdown in Argentina. There was a tendency for participants to report time passing more quickly than normal. A faster passage of time was associated with being a woman, of younger age andmorephysically active. A slower passage of time wastherefore associated with being a man, of older age and less physically active. The results indicate that whilst distortions to the passage of time during the covid-19 crisis appear to be aglobal phenomenon, cross-cultural differences are apparent in the factors which influence temporal experience.